Effects of selenium on structure of the essential oil isolated from Satureja hortensis L. (Lamiaceae) under the cadmium stress - Iraj Azizi; Mohammad Asadi (International Journal of Secondary Metabolite)
One of the heavy metals which cause severe environmental pollution and biochemical changes in plants is Cadmium (Cd) while Selenium (Se) acts as an important anti-stress agent in plants. In the present research, the glasshouse experiment was conducted to examine the effect of Cd and Se on structure of the essential oil isolated from the savory plant, Satureja hortensis L. To do so, the plants were polluted with different Cd levels including 0 (the control), 75, 100, and 150 µM. Moreover, Se was used in the form of sodium selenite salt in concentrations of 0 (control), 10, 20, and 40 µM. The results show that carvacrol was the main constituent in most of the essential oil analyses, except for one of them (0 µM of Cd×10 µM of Se). Furthermore, differences among minor constituents in most of treatments were not significant. Therefore, these results indicate the role of Cd and Se in the compositional changes of S. hortensis essential oil.